A Study on the Effect of Waiting Time of Ships at Anchor on Efficiency Measurement in Ports - Saip Onurhan Kadıoğlu; Murat Yorulmaz; Soner Esmer (İşletme Bilimi Dergisi)
Maritime transportation has an important share in international trade. With the advancement of communication and technology, speed has become a very important parameter in customer demands. Both the production and logistics sectors are making improvements to reduce lead times in response to this demand. The initial investment cost is quite high in ports, which play an important role in maritime trade. In addition, the return on investment is long. In order to shorten the return on investment and increase the profitability of the port, the port should be operated efficiently and effectively. On the other hand, the services provided at ports are directly related to the foreign trade performance of countries. Additional ship waits at ports will lead to additional costs, thus reducing the competitiveness of countries. The fact that ports are complex and dynamic service businesses causes efficiency measurements to be multivariate. Accordingly, this study focuses on only one specific area of the highly complex issue of port performance measurement. In this context, firstly, the basic literature on efficiency measurement in ports is given in the study, then, within the scope of the constraints of the study, Torosport Ceyhan's ship anchorage waiting times over a two-year period are focused and a research process is carried out in this context. According to the findings obtained by Pareto analysis in the Six Sigma approach, it was revealed that the most important reason for the ships waiting to dock at the port was "pier occupancy (56.8%)".